Sí se puede: The enduring legacy of Mexico on wine and politics - Daniel H. Chitwood; Luis Delaye; Cristina Domínguez‐Castro; Antonio Hernández‐López; Xavier López‐Medellín; Diana Margarita Mojica‐Muñoz; Alejandra Rougon‐Cardoso (Plants, People, Planet)
Societal Impact Statement The cultural significance of the grapevine is undeniable. However, we fail to acknowledge how the grapevine has and continues to influence the most pressing political questions of our time. From the beginning of the Conquest, Indigenous peoples were forced to plant the vine, Spain burned the vines Miguel Hidalgo used to teach the poor, and César Chávez and the Delano grape strike demanded justice for agricultural laborers. From the Grito de Dolores to Sí se puede, we demonstrate how the continuing relationship between Mexico and the grapevine influences debates surrounding labor, immigration, and human rights in the United States and throughout the world. To enhance the reach of this work, a Spanish language version of the paper is available in the Supporting Information (see Translation_ES). Summary The wild grapevine species (Vitis spp.) that comprise the pedigrees of rootstocks, the Americas as the source (and solution) to the Phylloxera crisis that decimated European vineyards, and California as a premier wine‐growing region are the topics that usually frame the history of grapes in North America. This Anglo‐American perspective ignores that domesticated grape varieties were first introduced to North America in what is now Mexico and the singular contributions of Mexican labor to the California wine economy that continue to influence politics. Here, we highlight the neglected history of grapevines in Mexico and argue that the politics of labor that played out during the Conquest never ceased and still shape debates surrounding immigration. Beginning with Hernán Cortés, Indigenous peoples were forced to plant grapevines and when they were successful, they were abruptly forbidden by Spain to grow grapes. This interference influenced Miguel Hidalgo, who taught the poor viticulture as a trade and who would lead the Mexican War of Independence and pay with his life. The grapevine continued its journey north to California, where Franciscans established the missions and cultivated the Mission grapes, which had lasting impacts on the genetics of grapevine varieties. Finally, it was the Delano grape strike that coalesced César Chávez and the United Farm Workers to demand justice for agricultural laborers that is the foundation of the California wine economy and still shapes the current political debate of immigration, labor, and human rights between the United States and Mexico.